Legal Force Of Electronic Land Sale And Purchase Deeds (E-Ajb) In The Digital Land Registration System After The Implementation Of Electronic Land Deed Official Services - Aditya Nugraha, I Gede Putu Dharma; Setyawati, Setyawati; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2026)
The digital transformation of land services through the implementation of electronic Land Deed Official (PPAT) services has given rise to innovations in the form of Electronic Land Sale and Purchase Deeds (e-AJB) within the digital land registration system. The presence of e-AJB raises legal issues related to its legal standing and force as an authentic deed in the Indonesian land law system. This study uses a normative legal research method (normative juridical) with a statutory, conceptual, case, and comparative approach. The data used are primary, secondary, and tertiary legal materials analyzed descriptively and qualitatively. The results of the study indicate that normatively e-AJB has received recognition through regulations related to electronic systems and electronic signatures, particularly the Electronic Information and Transactions Law and its implementing regulations. However, from a classical civil law perspective that requires physical presence and written document form as elements of an authentic deed as regulated in Article 1868 of the Civil Code, there is still debate regarding the fulfillment of the formal requirements of e-AJB as an authentic deed that has perfect evidentiary power. The main obstacles in the implementation of e-AJB include disharmony of laws and regulations, differences in interpretation regarding the physical presence of the parties, and aspects of security and proof of electronic signatures in the trial process. The Denpasar District Court decision is an important precedent that shows the need for harmonization of regulations between civil law, agrarian law, and information technology law to ensure legal certainty and protection for the parties. Thus, strengthening the legal basis of e-AJB through legislative updates and affirmation of its position in the hierarchy of laws and regulations is urgent to support the sustainability of the digital land registration system in Indonesia.